Gerakan Demiliterisasi Di Era Transisi Demokrasi: Peta Masalah Dan Pemanfaatan Peluang - Arie Sujito (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
Since the fall of New Order Regime, Indonesia has begun a new era of democratization. One of the important issues is the reformulation of civi-military relation. The practice of militarization and militarism-which is strong enough in Indonesia is considered as a fundamental waylay for the development of civil society path to democratization. Political reform in Indonesia constitutes a strategic momentum for demiliterization movement, namely posing military professionally under the civil political control democratically.